Esporulación de Cercospora fijiensis en diferentes ambientes - Williams Bailey, Carl W. (CATIE, Turrialba (Costa Rica), 2015)
The effect of growth culture, temperature, ilumination and mode of conidia collecting on the sporulation of Cercospora fijiensis were studies. Highest sporulation was on V8 juice agar. The best mode of conidia collection was by scraping, flooding with sterile water and discarding of the suspension of 12 day old cultures and collecting the conidia four days later. Greater sporulation was attained with alternating lighting (12 hours) and fluctuated temperature 21 - 30°C.